Do ferrous iron-oxidizing acidophiles (Leptospirillum spp.) disturb aerobic bioleaching of laterite ores by sulfur-oxidizing acidophiles (Acidithiobacillus spp.)? - Hetz, Stefanie A.; Schippers, Axel (Frontiers in Microbiology, 2024)
The extraction of nickel, cobalt, and other metals from laterite ores via bioleaching with sulfuroxidizing and ferric iron-reducing, autotrophic, acidophilic bacteria (e.g. Acidithiobacillus species) has been demonstrated under anaerobic as well as aerobic conditions in experiments in different laboratories. This study demonstrated the bioleaching of laterites from Brazil with the addition of elemental sulfur in 2 L stirred-tank bioreactors with pure and mixed cultures of Acidithiobacillus and Sulfobacillus species under aerobic conditions. In particular, a potential disturbance of mineral dissolution under aerobic conditions by ferrous iron-oxidizing acidophiles likely introduced as contaminants in an applied bioleaching process was investigated with Leptospirillum ferrooxidans at 30 °C and Leptospirillum ferriphilum at 40 °C, at maintained pH 1.5 or without maintained pH leading to an increase in acidity (with pH values < 1.0) due to the biological production of sulfuric acid. Despite the proportion of ferrous iron to the total amount of extracted iron in solution being drastically reduced in the presence of Leptospirillum species, there was a negligible effect on the extraction efficiency of nickel and cobalt, which is positive news for laterite bioleaching under aerobic conditions.